1731. Disseminated Metacestode Infection Due to an Unknown Versteria Species. (26th November 2018) - Lehman, Bethany; Leal, Sixto; Procop, Gary W; O'Connell, Elise M; Nash, Theodore; Jones, Stephen; Braunthal, Stephanie; Cruise, Michael; Mukhopadhyay, Sanjay; Banzon, Jona
Abstract: Background: A 68-year-old woman with hypogammaglobulinemia and prior treated lymphoma presented with fever and abdominal pain. Evaluation revealed numerous nodules in the lung, eye, brain, and liver (Figure 1). Initial lung and liver biopsies showed necrotizing granulomas with no organisms and negative serology and cultures. After progression while on broad-spectrum antibiotics for 4 months, an open liver biopsy revealed numerous nodular lesions and a mass made up of multifocal coalescing cystic lesions. The mass consisted of a degenerating 3-layered membrane without scoleces characterized by a wavy protuberant ciliated eosinophilic outer layer, subjacent degenerating cells with pyknotic nuclei, and loose connective tissue suggestive of a bladder wall and calcareous corpuscles in a matrix of granulomatous inflammation with areas of necrosis (Figure 2). This was diagnostic of disseminated metacestodes (larval stage) of a cestode (tapeworm). Treatment with praziquantel and albendazole led to improvement of symptoms and lesions. Disseminated cestode infections other than due to Echinococcus species are rare in humans. Sequencing was pursued due to the unusual findings. Methods: DNA was extracted from liver tissue followed by targeted amplification of the cestode COX1 gene. PCR products confirmed to be 134 bp, as expected for a cestode COX1 gene, then inserted into a 2.1 Topo vector and cloned. Five separate isolates were sequenced, and 4 were interpretable. The 129-bp consensus sequence is shown in Figure 3. Basic Local Alignment Search Tool (NCBI BLAST) was used to find highly similar sequences. Results: The sequence matched to Versteria sp. ( T. mustelae ) COX1 gene from a mink in Oregon (accession KT223034) with 98% identity. Conclusion: Metacestodes have the propensity to proliferate and rarely disseminate. There is one reported case of Versteria sp. causing a lethal disseminated infection of an orangutan. This is the first report of a Versteria sp. disseminated infection in a human and is singular because the patient survived. The patient likely accidentally ingested ova shed from a tapeworm in a mink or similar mammalian host. Histopathologic assessment is crucial in diagnosing cestode infection. COX1 gene sequencing is useful for cestode identification. Disclosures: All authors: No reported disclosures.